FGFC1 Selectively Inhibits Erlotinib-Resistant Non-Small Cell Lung Cancer via Elevation of ROS Mediated by the EGFR/PI3K/Akt/mTOR Pathway - Yan, Shike; Zhang, Bing; Feng, Jingwen; Wu, Haigang; Duan, Namin; Zhu, Yamin; Zhao, Yueliang; Shen, Shuang; Zhang, Kai; Wu, Wenhui; Liu, Ning (Frontiers in Pharmacology, 2022)
Non-small cell lung cancer (NSCLC) is one of the most common malignancies in the world. Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) have been used as a first-line treatment for patients with EGFR mutations in advanced NSCLC. Nevertheless, the drug resistance considerably limits its clinical efficacy. Therefore, it is of great importance to develop new chemotherapeutic agents and treatment strategies. FGFC1 (Fungi fibrinolytic compound 1), a type of bisindole alkaloid from a metabolite of the rare marine fungi Starchbotrys longispora. FG216, has exhibited good fibrinolytic activity and anti-inflammatory activity. However, the potent efficacy of FGFC1 in human cancers requires further study. Herein, we demonstrated that FGFC1 selectively suppressed the growth of NSCLC cells with EGFR mutation. Mechanistically, FGFC1 treatment significantly induced the apoptosis of H1975 erlotinib-resistant NSCLC cells in a dose-dependent manner, which was proved to be mediated by mitochondrial dysfunction and elevated accumulation of intracellular reactive oxygen species (ROS). Scavenging ROS not only alleviated FGFC1-induced apoptosis but also relieved the decrease of phospho-Akt. We further confirmed that FGFC1 significantly decreased the phosphorylation of protein EGFR, PI3K, Akt, and mTOR in H1975 cells. Notably, PI3K inhibitor (LY294002) could promote the accumulation of ROS and the expression levels of apoptosis-related proteins induced by FGFC1. Molecular dynamics simulations indicated that FGFC1 inhibited EGFR and its downstream PI3K/Akt/mTOR signaling pathway through directly binding to EGFR and showed a much higher binding affinity to EGFRT790M/L858R than EGFRWT. Additionally, FGFC1 treatment also inhibited the migration and invasion of H1975 cells. Finally, FGFC1 effectively inhibited tumor growth in the nude mice xenograft model of NSCLC. Taken together, our results indicate that FGFC1 may be a potential candidate for erlotinib-resistant NSCLC therapy.